2018
DOI: 10.1007/s11665-018-3181-5
|View full text |Cite
|
Sign up to set email alerts
|

Processing and Characterization of Fe-Mn-Cu-Sn-C Alloys Prepared by Ball Milling and Spark Plasma Sintering

Abstract: In this work, Fe-Mn-Cu-Sn-C alloys were prepared by means of powder metallurgy (PM). Powder mixtures were ball-milled for 8, 30 and 120 h and densified to < 1% porosity using spark plasma sintering (SPS) at 900°C and 35 MPa. After consolidation, all samples of the Fe alloys were characterized by x-ray diffraction (XRD), scanning electron microscopy (SEM), hardness and flexural strength tests. Resistance to abrasive wear was evaluated in both three-body abrasion and two-body abrasion tests. The SEM observations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…Previous studies clearly indicate that reinforcing the metal matrix with dispersed ceramic particles could improve the quality and efficiency of metallic-diamond tools. Our previous work [ 15 , 16 ] confirmed that inexpensive Fe–Mn–Cu–Sn–C material can be a promising alternative to expensive Co-20% WC alloys in some sintered diamond tools. The Fe–Mn–Cu–Sn–C composites obtained by SPS (at 900 °C/35 MPa) had a hardness of 319 ± 32 HV1, high bending strength (σTRS > 1200 MPa) and bending yield strength (σ0.2 > 1000 MPa), and significantly better wear resistance than other commercial composites due to Feγ twinning and the martensitic transformation induced by plastic deformation in the sub-layer as a result of abrasion, which increases hardness and strength.…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…Previous studies clearly indicate that reinforcing the metal matrix with dispersed ceramic particles could improve the quality and efficiency of metallic-diamond tools. Our previous work [ 15 , 16 ] confirmed that inexpensive Fe–Mn–Cu–Sn–C material can be a promising alternative to expensive Co-20% WC alloys in some sintered diamond tools. The Fe–Mn–Cu–Sn–C composites obtained by SPS (at 900 °C/35 MPa) had a hardness of 319 ± 32 HV1, high bending strength (σTRS > 1200 MPa) and bending yield strength (σ0.2 > 1000 MPa), and significantly better wear resistance than other commercial composites due to Feγ twinning and the martensitic transformation induced by plastic deformation in the sub-layer as a result of abrasion, which increases hardness and strength.…”
Section: Introductionmentioning
confidence: 84%
“…Spongy iron, ground ferromanganese, and water-atomized tin-bronze powders were provided by Höganäs AB, Höganäs, Sweden, ESAB, Katowice, Poland and Neochimie, Saint-Ouen-l’Aumône, France, respectively. The powder mixture contained 12 wt.% Mn, 6.4 wt.% Cu, 1.6 wt.% Sn, and 0.6 wt.% C and was prepared as described in [ 15 , 16 ]. The powders SiC (F320 series, Washington Mills Electro Minerals, Manchester, England, UK), Al 2 O 3 (EF-320 series, Stanchem Sp.zoo, Niemce, Poland), and ZrO 2 (Yttria-stabilized Zirconia Powder (3-YSZ) GRADE 16, HC Starck, Goslar, Germany) were used as ceramic phases to modify the material.…”
Section: Methodsmentioning
confidence: 99%
“…Spark plasma sintering(SPS), as a new sintering technology of powder metallurgy, has the advantages of uniform heating, fast heating, low sintering temperature, short sintering time and easy microstructure control, which can be used to prepare high performance nanocrystalline or ultrafine metal materials 26,27 . High density Fe-Mn alloys were prepared by ball milling and SPS 28 . The nanocrystalline Fe-Mn alloy was prepared by SPS technique with a yield strength of 1428 MPa in compression test 29,30 .…”
Section: Introductionmentioning
confidence: 99%
“…Among these methods, the SPS (Spark Plasma Sintering) method is the most widespread. This technology allows for the obtaining of a wide range of materials [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%